Pengaruh Motivasi, Disiplin Kerja dan Kompensasi Terhadap Kinerja Karyawan KFC Mall Metropolitan Bekasi - Primaraga Sumantri Indra Wicaksana (MAMEN: Jurnal Manajemen, 2022)
The purpose of this research was to determine the effect of motivation, work discipline and compensation on employee performance at KFC metropolitan mall Bekasi branch. This type of research is quantitative with three independent variables consisting of Motivation (X1), Work Discipline (X2) and Compensation (X3) and the dependent variable of employee performance (Y). Samples were taken using the Slovin method and a population of 49 employees and a sample of 44 employees was obtained. The collected data was then analyzed using Validity Test, Reliability Test, Classic Assumption Test, Multiple Linear Regression Analysis, Hypothesis Testing and Coefficient of Determination, with the help of SPSS Version 22 For Windows program. The results of the study can be seen that motivation, work discipline and compensation have a significant effect on employee performance, this is strengthened by the T test. T count = 6.839 with a significant 0.001 <0.05 so that the hypothesis can be accepted. The results of the study show that motivation, work discipline and compensation have been shown to affect employee performance at the KFC metropolitan mall branch in Bekasi. So leaders must be able to motivate their employees and exemplify good discipline at work and must also be able to pay attention to the welfare of employees by providing good compensation for their employees.